Impact of tension stiffening on the tensile and flexural behavior of ECC ferrocement. (25th April 2022) - Do, Tuong Dat Dinh; Yen, Kai-Jian; Yen, Cheng-Hao; Hung, Chung-Chan
Highlights: Adding wire mesh in ECC substantially enhanced strength and crack control. The average crack spacing decreased with a smaller wire and larger mesh content. The use of a larger wire diameter led to more pronounced tension stiffening effect. The flexural models reasonably predicted the flexural strength of ECC ferrocement. Sensitivity of ECC compressive strain on accuracy of flexural models was studied. Abstract: Ferrocement is a type of thin walls constructed of hydraulic cement mortar reinforced with closely spaced layers of wire mesh. Although the applications of ferrocement have been common, there has been a limited number of studies on the development of new ferrocement composites. Particularly, premature failure could occur to ferrocement due to the vulnerability of spalling and delamination. Engineered cementitious composite (ECC) is characterized by its ductile strain-hardening behavior and crack width control under direct tension. To enhance the mechanical properties and crack width control of ferrocement, the potential for using ECC to replace cement mortar in conventional ferrocement, termed ECC ferrocement, was explored. The influences of the volume fraction, wire size, and wire spacing of the steel mesh on the mechanical properties of ECC ferrocement under tension and flexure were studied. It was found that while ECC ferrocement had substantially enhanced strength and crack width control compared to pure ECC and conventional ferrocement, there was a relatively limited improvement in the deformation capacity. The test results also showed that the interaction between the embedded steel mesh and the surrounding ECC led to a pronounced tension stiffening effect, which significantly enhanced the uniaxial and flexural strengths of ECC ferrocement. In addition to the experimental study, three flexural models, including a rigorous implicit model and two simplified explicit models, were proposed to evaluate the flexural strength of ECC ferrocement. The comparisons between the experimental results and predicted strengths demonstrated that the proposed three models can reasonably predict the flexural strength of ECC ferrocement with an average error of less than 6% when the tension stiffening of ECC was accounted for. The results of parametric studies indicated that a variation in the ultimate ECC compressive strain ranging between 0.003 and 0.005 for the flexural models led to a negligible influence on the predicted flexural strength.